Beyond capital and wealth - Dennis J. Snower (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The world is economically integrated, but socially fragmented. Thus economic progress can become decoupled from social progress. As long as social progress is closely linked to and flows from economic progress, it is appropriate for government to focus attention on economic policy to promote economic growth. Indeed, for at least the first four decades of the postwar period, there are good reasons to believe that this was broadly the case for most developed economies. Then, starting in the 1980s and accelerating after the financial crisis of 2008, we argue that social progress in these countries became progressively decoupled from economic progress. The result has been the phenomenon of misery in the midst of plenty: despite continued economic growth, we witness rising dissatisfaction among large segments of the public, declining trust in most public and private institutions, rising nationalism and populism, rising discontent with globalization, increasing unwillingness to accept migrants and refugees, and growing ethnic and religious conflicts. This paper argues that the prevailing thinking about government policy is an outgrowth of the Age of Coupling. In the Age of Decoupling, however, a radically different approach to government policy is required, one that focuses not just on material wellbeing and its distribution, but also on promoting people's sense of empowerment and social solidarity.
Keywords: F5; H7; 330; G20; governance; international cooperation; empowerment and solidarity